Active Surveillance of Maternal Mortality in New York City - Pallin, Daniel J. (© American Journal of Public Health 2002, 2002)
Objectives. This study examined the usefulness of computer-assisted active surveillance in identifying maternal deaths in New York City. Methods. Computerized searches of hospital discharge and autopsy record databases were conducted for maternal deaths occurring in 1997. Results. Active surveillance revealed 14 new maternal deaths not previously reported, an 88% increase. Nine of these deaths were found through the hospital discharge database search, 1 was found through the autopsy record search, and 4 were found in both searches. Overall maternal mortality ratios associated with active surveillance and routine surveillance were 24.3 and 13.0 deaths per 100 000 live births, respectively. Conclusions. Active surveillance of maternal mortality is useful in identifying new maternal deaths. Existing databases can be used relatively easily to augment routine surveillance of maternal mortality.